Optical properties of small polaron in Mn1.56Co0.96Ni0.48O4 films investigated by temperature-dependent transmission spectra. (21st January 2015) - Wu, J; Ouyang, C; Zhou, W; Gao, Y Q; Hou, Y; Huang, Z M; Chu, J H
Abstract: Temperature-dependent transmission spectra of Mn1.56 Co0.96 Ni0.48 O4 (MCNO) films on Al2 O3 substrate have been measured in 1.5–5.5 μ m wavelength range. A dispersion relation that combines Lorentz oscillator model and Cauchy model is successfully adopted to describe the optical properties of small polaron in MCNO films. An absorption peak at around 0.8 eV which corresponds to the center energy of Lorentz oscillator is unveiled to be due to the small polaron hopping from Mn 3+ state (lower Hubbard band) to Mn 4+ state (upper Hubbard band). The regularity of temperature dependent peak position shows that above the magnetic transition temperature (∼200 K) the peak position varies slightly, while below this temperature it varies more obviously. This phenomenon can be explained by the fact that the buildup of magnetic order leads to the localized electron states gradually withdrawing from the Hubbard band gap.